Ways to Improve Government Subsidy Policies for Higher Educational Institutions to Enhance the Employment Rate of Their Graduates - Kyewoo Lee; Miyeon Chung (Korea Development Institute (KDI), 2015)
As high rates of youth unemployment have been a prominent social issue, the government should seek to alter fiscal subsidy policies for higher educational institutions in such a way that increases the employment prospects of university graduates, and should also place a greater focus on performance indicators, which affect the employment rates, such as the level of scholarship benefits, the student-faculty ratio, and education spending per student. - On top of socioeconomic factors, structural problems inherent to the higher education system also contribute to high youth unemployment rates. - The deregulation of university establishment led to a spike in the number of higher education institutions, contributing to the 'dumbing-down' of higher education. - Government subsidy for higher education has increased every year, which calls for an efficiency-driven approach. - This study focuses on unemployment, one of the country's most pressing social issues, and proposes policy plans to increase the employment rate through fiscal assistance programs, carried out in order to ensure that government financial support for higher education can generate greater policy effects. - The government has established a series of indicators related to university education and has provided financial support based on a predetermined formula using these indicators. As such, the objective of government financial support is to improve the quality of higher education by seeking improvement among selected education indicators. - The selection of education indicators and their corresponding weighting is a process that lacks objective and empirical effectiveness analysis, and the weights are inconsistent over time, a challenge to the effectiveness of fiscal subsidy programs. - To effectively implement government-financed university projects, it is imperative to clearly define the ultimate objectives of such projects and empirically identify factors contributing to the achievement of these objectives. In addition, it is most efficient to differentiate the allocation of financial resources among universities according to their contribution to achieving the ultimate objectives. - This study defines the employment rate as an output of education and identifies input variables of university education, which affect the employment rate, in order to empirically analyze and review the extent to which such variables affect the improvement of employment rate. - Educational spending per student, student-faculty ratio, the proportion of scholarship benefits are three factors that have statistically significant impact on employment rate. - The analysis of an interaction effect between the per-student spending and the student-faculty ratio indicators confirmed the existence of interaction effects. When the per-student spending is above a certain level, the employment rate increases regardless of any increase in the student-faculty ratio. - It is recommended that the government recognize the employment rate as the principal indicator of the quality of education offered at higher education institutions and provide financial support for them with priority weights on the three indicators that have an empirically proven impact on the employment rate. In addition, it is crucial that higher educational institutions' continued improvement in these three areas is monitored more closely.
Keywords: 330